A nine-level T-type inverter (9L-TTI) with voltage boost capability - Firdous Z.; Mekhilef S.; Mishra N.; Mustafa A.; Seyedmahmoudian M.; Stojcevski A. (John Wiley and Sons Inc, 2024)
This paper introduces a 9L T-type boost inverter (9L-TTI) based multilevel topology, which generates a nine-level output voltage in the boost mode. This topology uses 12 switching elements alongside less voltage stress and one switched capacitor unit. This is the significant advantage of the mentioned topology. Following the discussion of the advantages of the provided design, a comparative study is conducted. This results in a reduction in device counts, cost-effectiveness, and voltage stress on the devices. For switching scheme, fundamental switching frequency-based modulation is incorporated by having nearest level control (NLC) technique. For proper validation of this work, it is also demonstrated through test results. Here the results are demonstrated at different load conditions, which include resistive and inductive loads. Further, it is demonstrated at different modulation indices and total harmonic distortion (THD) of converter voltage and current for RL-load, is validated from the power quality improvement point. 2023 The Authors. IET Power Electronics published by John Wiley & Sons Ltd on behalf of The Institution of Engineering and Technology.